Crystallization products of risedronate with carbohydrates and their substituted derivatives - Kos, Jiri; Pentakova, Monika; Oktábec, Zbyněk; Krejcik, Lukas; Mandelova, Zuzana; Harokova, Pavla; Hruskova, Jana; Pekarek, Tomas; Dammer, Ondřej; Tkadlecova, Marcela; Havlicek, Jaroslav; Vinsova, Jarmila; et al. (Molecules, 2011)
The gastrointestinal absorption of bisphosphonates is in general only about 1%. To address this problem mixtures of risedronate monosodium salt with twelve varied sugar alcohols, furanoses, pyranoses and eight gluco-, manno- and galactopyranoside derivatives as counterions were designed in an effort to prepare co-crystals/new entities with improved intestinal absorption. Crystalline forms were generated by means of kinetically and/or thermodynamically controlled crystallization processes. One hundred and fifty-two prepared samples were screened by means of FT-NIR and FT-Raman spectroscopy. No co-crystal was prepared, but noteworthy results were obtained. A new solid phase of risedronate monosodium salt generated in the presence of phenyl-β-d-galactopyranoside under thermodynamically controlled crystallization conditions was found and also characterized using solid state NMR spectroscopy, X-ray powder diffraction and differential scanning calorimetry. This new polymorph was named as form P. Interactions between risedronate monosodium salt and both carbohydrates were confirmed by means of molecular dynamics simulation. In the present study the relationships between the chemical structures of the studied compounds required for crystalline form change are discussed.
Keywords: Spectrum Analysis, Raman; molekulární struktura; Calorimetry, Differential Scanning; Crystallization; Galactosides; X-Ray Diffraction; magnetická rezonanční spektroskopie; sacharidy; krystalizace; Etidronic Acid; difrakce rentgenového záření; Ramanova spektroskopie; galaktosidy; Carbohydrates; spektroskopie infračervená s Fourierovou transformací; kyselina etidronová; diferenciální skenovací kalorimetrie; Magnetic Resonance Spectroscopy; Spectroscopy, Fourier Transform Infrared; Molecular Structure